Performance Characterizations of a Simultaneous "AND"-"OR" Gates System Dependent on a Parallel-Series SOA-MZIs Combination - Termos, Hassan; Kallas, Kassem (Journal of Electronics and Electrical Engineering, 2026)
In this study, we experimentally investigate a simultaneous "AND"-"OR" all-optical logic gate system based on a series-parallel configuration of Semiconductor Optical Amplifier Mach-Zehnder Interferometers (SOA-MZIs). The proposed "AND" gate exploits the Cross-Phase Modulation (XPM) effect at the outputs of two parallel SOA-MZIs, while the "OR" gate, connected in series with the parallel stage, relies on Cross-Gain Modulation (XGM) in the third interferometer (SOA-MZI3). The system performance is evaluated in the optical, electrical, and temporal domains. Several performance metrics are considered, including power scaling, optical conversion efficiency, Optical Signal-to-Noise Ratio (OSNR), and Error Vector Magnitude (EVM), in order to characterize the generated optical "AND" and "OR" logic signals. Using an optical pulse source operating at 1550 nm with a pulse width of 1.3 ps and a repetition rate of 20 GHz, the proposed parallel-series SOA-MZI architecture produces up to 11 dBm of average output power with a conversion gain of 21 dB for the "OR" signal. At the SOA-MZI outputs, the maximum achievable bit rates for 64-QAM-modulated "AND" and "OR" signals reach 80 Gbit/s and 100 Gbit/s, respectively, at a common harmonic frequency of 80 GHz. The simultaneous logic gate system also demonstrates excellent optical performance, with optimal OSNR values of 61 dB for the "AND" signal and 82 dB for the "OR" signal. The generated "AND" and "OR" pulses exhibit temporal durations of 7.7 ps and 11.1 ps, respectively, at 1550 nm. In addition, the output beams show high spatial quality, with a beam-propagation factor M2 < 1.74.